Ceftriaxone Relieves Trigeminal Neuropathic Pain Through Suppression of Spatiotemporal Synaptic Plasticity via Restoration of Glutamate Transporter 1 in the Medullary Dorsal Horn - Luo, Xiao; He, Ting; Wang, Yan; Wang, Jiang-Lin; Yan, Xue-Bin; Zhou, Hao-Cheng; Wang, Rui-Rui; Du, Rui; Wang, Xiao-Liang; Chen, Jun; Huang, Dong (Frontiers in Cellular Neuroscience, 2020)
Using a rat model of trigeminal neuropathic pain (TNP) produced by chronic compression of the infraorbital nerve (CCI-ION), we investigated the analgesic effect and the underlying mechanisms of ceftriaxone (Cef), a -lactam antibiotic, that is thought to be a potent stimulator of glutamate transporter 1 (GLT-1). First, repeated intraperitoneal (i.p.) injections of Cef (200 mg/kg) for 5-days since Day 1 of CCI-ION could significantly relieve both mechanical and thermal pain hypersensitivity from day 10 after drug administration. Western blot and immunofluorescent results demonstrated that 5-days administration of Cef resulted in restoration of GLT-1 expression to a level equivalent to the sham control which was dramatically lost under the TNP condition. Moreover, multi-electrode (8x8) array recordings of network field excitatory postsynaptic potentials (fEPSPs) were performed on the acutely dissociated medullary dorsal horn slice evoked by electrical stimulation of the trigeminal spinal tract. The results showed that the increased number of fEPSPs, induction rate and maintenance of long-term potentiation caused by CCI-ION were significantly suppressed by 5-days administration of Cef. Taken together, the results indicate that Cef can relieve TNP through suppression of spatiotemporal synaptic plasticity via GLT-1 restoration in the medullary dorsal horn of the trigeminal nerve.